M Keris Sumenep Sebagai Alat Akuntansi Kultural : Penilaian, Pencatatan, dan Pengelolaan Warisan Budaya: Keris sumenep,Akuntansi kultural, Penilaian, Pencatatan, dan Pengelolaan - Mery, MeryPutriFaradina; Djasuli, Mohamad Djasuli (JURNAL EKBIS, 2024)
This research aims to explore the meaning of "Accounting" in the practices of Sumenep keris craftsmen with a focus on cultural values, mindset, lifestyle and community beliefs. Qualitative ethnographic methods were used in three craftsman centers, namely Saronggi, Bluto, and Lenteng. His findings highlight the "Cultural Accounting" model of the first keris craftsmen, assessment is based on the religious philosophy "Sustenance is not mathematics that must be calculated" and accounting is understood as "Knowledge". Second, simple recording which is different from conventional accounting. Third, the management reflected in bookkeeping is not like ordinary accounting reports. The results show that there is a distinctive accounting model of keris craftsmen which is inseparable from local culture, making a significant contribution to accounting practice.